Enhancing Neuroblastoma Immunotherapies by Engaging iNKT and NK Cells - McNerney, Kevin O.; Karageorgos, Spyridon A.; Hogarty, Michael D.; Bassiri, Hamid (Frontiers in Immunology, 2020)
Neuroblastoma (NB) is the most common extracranial solid tumor in children and, in the high-risk group, has a 5-year mortality rate of approximately 50%. The high mortality rate and significant treatment-related morbidities associated with current standard of care treatment belie the critical need for more tolerable and effective treatments for this disease. While the monoclonal antibody dinutuximab has demonstrated the potential for immunotherapy to improve overall NB outcomes, the 5-year overall survival of high-risk patients has not yet substantially changed. The frequency and type of invariant natural killer T cells (iNKTs) and natural killer cells (NKs) has been associated with improved outcomes in several solid and liquid malignancies, including NB. Indeed, iNKTs and NKs inhibit tumor associated macrophages (TAMs) and myeloid derived suppressor cells (MDSCs), kill cancer stem cells (CSCs) and neuroblasts, and robustly secrete cytokines to recruit additional immune effectors. These capabilities, and ¬promising pre-clinical and early clinical data suggest that iNKT- and NK-based therapies may hold promise as both stand-alone and combination treatments for NB. In this review we will summarize the biologic features of iNKTs and NKs that confer advantages for NB cellular immunotherapy, discuss the barriers imposed by the NB TME, and examine the current state of such therapies in pre-clinical models and clinical trials.